Biological Potential of Thiazole Derivatives of Synthetic Origin. (7th March 2017) - Mishra, Raghav; Sharma, Pramod Kumar; Verma, Prabhakar Kumar; Tomer, Isha; Mathur, Garima; Dhakad, Prashant Kumar
Abstract : Thiazole and related nucleus are one of the most important potential entities in the largely growing chemical world of heterocyclic compounds exhibiting remarkable pharmacological activities. The knowledge of various synthetic pathways and diverse physicochemical parameters of such compounds draw the especial attention of medicinal chemists to produce combinatorial library and carry out exhaustive efforts in the search of lead molecules. The similar compounds synthesized through different routes bear variable magnitudes of biological activities. The present review highlights a broad view on biological activities of compounds having thiazole nucleus. Abstract :